2022
DOI: 10.1007/s11442-022-1981-x
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale analysis of trade-off/synergistic effects of forest ecosystem services in the Funiu Mountain Region, China

Abstract: The trade-offs and synergies of forest ecosystem service are important research topics for several disciplines. The multi-scale analysis of service trade-offs and synergies assists in the implementation of more effective forest resource management. Based on multi-source data including forest distribution, topography, NDVI, meteorology and soil conditions, key forest ecosystem services, including total forest volume, carbon storage, water yield, soil retention and habitat quality were mapped and evaluated for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…For these reasons, huge benefits would result from resolving environmental crises and improving the overall benefits of ecosystem services, by increasing the area devoted to natural forests in the GRB. Similar to existing research on plantation ecosystem services [5,46,53,54], trade-offs among ecosystem services in plantations in the GRB can be easily found for carbon storage and water yield, or volume accumulation and soil retention, and they result in soil erosion and water pollution problems. Therefore, plantation management should pay attention to upgrading the tending, logging and conservation engineering measures needed to increase the overall benefits of ecosystem services.…”
Section: Discussionmentioning
confidence: 69%
“…For these reasons, huge benefits would result from resolving environmental crises and improving the overall benefits of ecosystem services, by increasing the area devoted to natural forests in the GRB. Similar to existing research on plantation ecosystem services [5,46,53,54], trade-offs among ecosystem services in plantations in the GRB can be easily found for carbon storage and water yield, or volume accumulation and soil retention, and they result in soil erosion and water pollution problems. Therefore, plantation management should pay attention to upgrading the tending, logging and conservation engineering measures needed to increase the overall benefits of ecosystem services.…”
Section: Discussionmentioning
confidence: 69%
“…It is difficult to achieve the superposition of different services on the pixel scale, because of the differences in indicators unit. Here, based on the study (Zhang et al, 2022a), we developed a process for overlaying indicators and performing trade‐off/synergy. The details are as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the supply capacities of the CS, SR, FM, and WC were relatively low, resulting in prominent strong trade-offs. In order to alleviate the strong trade-off among these services, policy makers should strengthen the management of secondary forests and plantation forests at the town scale, promote mixed coniferous and broadleaved forests to replace pure forests, and improve the supply capacity of CS, SR, and WC [29]. Nevertheless, at the 3000-m grid scale, construction land% had the strongest impact on high synergies of ESs.…”
Section: Multiscale Analysis Of the Effects Of Landscape Pattern On T...mentioning
confidence: 99%
“…Other studies indicated that ES synergies were enhanced as the scale increased [27,28]. Such a difference mainly stems from the unconformity of ecological conditions and processes at different scales or the spatial mismatch between the supply and demand of ESs [29]. In general, local residents pay more attention to provision services they can directly enjoy, such as food supply, while decision-makers attach more importance to regulating services (e.g., water conservation, flood mitigation, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation